Innovation within tradition: interesting insights from two small family bakeries - Floris, Michela; Dettori, Angela; Dessì, Cinzia (Piccola Impresa / Small Business, 2020)
The paper investigates how small family firms that are embedded in traditional industries and closed context adopt innovation. Building on the embeddedness construct and analyzing two exemplary cases of small bakeries, a model is proposed to highlight the role that local legitimization and target market play in innovation strategies. Findings contribute to academic and practitioners, showing interesting insights.